2014
DOI: 10.1021/bi500158w
|View full text |Cite
|
Sign up to set email alerts
|

Non-native Soluble Oligomers of Cu/Zn Superoxide Dismutase (SOD1) Contain a Conformational Epitope Linked to Cytotoxicity in Amyotrophic Lateral Sclerosis (ALS)

Abstract: Soluble misfolded Cu/Zn superoxide dismutase (SOD1) is implicated in motor neuron death in amyotrophic lateral sclerosis (ALS); however, the relative toxicities of the various non-native species formed by SOD1 as it misfolds and aggregates are unknown. Here, we demonstrate that early stages of SOD1 aggregation involve the formation of soluble oligomers that contain an epitope specific to disease-relevant misfolded SOD1; this epitope, recognized by the C4F6 antibody, has been proposed as a marker of toxic speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 41 publications
4
42
0
Order By: Relevance
“…Additionally, the recently discovered epitope of the C4F6 Ab (18), which preferentially binds the SOD1 trimer (Fig. S4A) as well as several other disease-linked SOD1 species (15,16) over the native dimer or monomer, is completely exposed on the surface of the trimer structure ( Fig. S4B), further supporting our model and suggesting the potential toxicity of the SOD1 trimer.…”
Section: Sod1 Trimer Features Nonnative Secondary Tertiary and Quatsupporting
confidence: 80%
See 4 more Smart Citations
“…Additionally, the recently discovered epitope of the C4F6 Ab (18), which preferentially binds the SOD1 trimer (Fig. S4A) as well as several other disease-linked SOD1 species (15,16) over the native dimer or monomer, is completely exposed on the surface of the trimer structure ( Fig. S4B), further supporting our model and suggesting the potential toxicity of the SOD1 trimer.…”
Section: Sod1 Trimer Features Nonnative Secondary Tertiary and Quatsupporting
confidence: 80%
“…These small, soluble oligomers undergo aberrant interactions with cell machinery and activate cell death pathways, but their exact stoichiometry is not known and their properties have yet to be characterized. Recently, metastable soluble Cu,Zn superoxide dismutase (SOD1) oligomers have been identified that contain an epitope associated with disease-linked species of SOD1, mutants of which are implicated in a subset of ALS (15)(16)(17)(18). Size exclusion chromatography (SEC) of these oligomers revealed a size range of two to four monomers, consistent with previous findings of potentially cytotoxic SOD1 oligomers (19)(20)(21).…”
supporting
confidence: 81%
See 3 more Smart Citations